A novel effective thermal conductivity correlation of the PCM melting in spherical PCM encapsulation for the packed bed TES system. (5th May 2018) - Liao, Zhirong; Xu, Chao; Ren, Yunxiu; Gao, Feng; Ju, Xing; Du, Xiaoze
Highlights: A validated numerical model was used to simulate the melting process in a capsule. The effective thermal conductivity correlations in the literature was discussed. A new effective thermal conductivity correlations was proposed. The proposed correlations shows better results than the reported correlations. Abstract: Packed bed thermal energy storage (TES) system with phase change material (PCM) encapsulation is one of the potential TES technologies for the solar thermal application. In present study, the constrained melting process of PCM in spherical encapsulation is simulated by a validated natural convection included model. This model is then used to simulate the melting processes of NaNO3 with different conditions. Meanwhile, the same melting processes are also calculated by the conduction controlled model with available effective thermal conductivity correlations reported in the literature. It is found that the changes of liquid fraction obtained from the natural convection included model and the conduction controlled model with the reported thermal conductivity correlations show obvious difference. Then, based on the simulating results of the cases using the natural convection included model, a new correlation for the effective thermal conductivity is proposed by linear regression. It shows that the conduction controlled model with the proposed effective thermal conductivity correlation gives better results on the change of liquid fraction than that with correlations reported in the literature. Therefore, the proposed correlation can be used to calculate the melting process of PCM in a capsule by the conduction controlled model, which is in urgent need for modeling of packed bed latent TES systems.